Menentukan Portofolio Optimal Menggunakan Model Markowitz - Nuralfira Putri Hartono; Onoy Rohaeni (UPT Publikasi Ilmiah Unisba, 2021)
The provider company on the covid-19 pandemic became an interest in investors to invest. Investing certainly has a risk then investors must have an analysis to know what to bear during investing is like making a portfolio. In determining the optimal portfolio there are several models that one of them can use is the Markowitz model. Specifies an optimal portfolio with Markowitz models only reserved for investors who want the smallest risk outcome with a particular profit. The results earned for the investor's optimal portfolio could instill its funds on each provider's shares, on W shares with a fund proportion of 0.48%, on X shares with a fund proportion of 50%, on Y shares with a fund proportion of 49.5% and on Z shares with a fund proportion of 0.11%. The optimal portfolio formed gives a portfolio return expectation of 7.53% with a portfolio risk or risk that investors will bear is as much as 9.95%. Perusahaan provider pada pandemi covid-19 menjadi ketertarikan para investor untuk berinvestasi. Berinvestasi tentunya memiliki risiko maka investor harus memiliki analisis untuk mengetahui apa yang akan ditanggung selama berinvestasi seperti membuat suatu portfolio. Dalam menentukan portfolio optimal ada beberapa model yang dapat digunakan salah satunya adalah model Markowitz. Menentukan portfolio optimal dengan model Markowitz hanya diperuntukan untuk investor yang menginginkan hasil risiko terkecil dengan keuntungan tertentu. Hasil yang diperoleh untuk portfolio optimal investor dapat menanamkan dananya pada masing-masing saham provider, pada saham W dengan proporsi dana sebesar 0,48%, pada saham X dengan proporsi dana sebesar 50%, pada saham Y dengan proporsi dana sebesar 49,5% dan pada saham Z dengan proporsi dana sebesar 0,11%. Portofolio optimal yang terbentuk memberikan return ekspektasi portfolio sebesar 7,53% dengan risiko portfolio atau risiko yang akan ditanggung oleh investor adalah sebesar 9,95%.